Quantification of endogenous and therapeutic IgG crossing the kidney barrier from bloodstream to urine - Eicher, Barbara; Esslinger, Christoph; Hillenbrand, Matthias (Frontiers in Pharmacology, 2025)
This study investigates the biodistribution of a therapeutic antibody from serum to urine across the kidney endothelial barrier, contextualizing the findings with existing literature. Our analysis shows the quantitative correlation between serum levels of the intravenously administered antibody rituximab and its urinary concentration, indicating a predictable pharmacokinetic profile. The results align with previous quantitative studies on the biodistribution of endogenous and vaccination induced IgG between serum and urine, confirming that recombinant therapeutic IgG1 passes the kidney endothelial barrier and exhibits similar biodistribution to endogenous IgG. These insights may inform the determination of optimal dosages for therapeutic antibodies targeting the urothelium or renal epithelium.